PENGARUH PRICE EARNING RATIO (PER) TERHADAP HARGA SAHAM DALAM KELOMPOK JAKARTA ISLAMIC INDEX (JII) TAHUN 2015-2018 - Sahrani; Febrianti, Asti; Nurhayato, St, (Funds: Jurnal Ilmiah Akuntansi, Keuangan, dan Bisnis, 2023)
The facts and the theory of stock prices, which holds that economic fundamentals and corporate fundamentals have an impact on stock prices, are at odds with one another. As a result, it is important to investigate financial parameters, one of which is the Price Earning Ratio. This study attempts to ascertain how the Price Earning Ratio has changed over time and how it has affected stock prices in the Jakarta Islamic Index group.This study's methodology is quantitative research, which collects data in numerical form. With this kind of associative research, the impact of one variable on other variables can be ascertained. Simple regression analysis, descriptive statistical assumption testing, and hypothesis testing are the data analysis techniques used.The findings of this study show that the Price Earning Ratio has a positive and significant impact on stock prices in companies listed on the Jakarta Islamic Index in 2015–2018, and investors should take this ratio into consideration. Based in part on the T test, the significance value for this ratio is 0.000 0.05.